2004
DOI: 10.1128/jb.186.22.7618-7625.2004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Control in Bacterial Regulatory Circuits

Abstract: We show that for two well-characterized regulatory circuits in Escherichia coli, Tn10 tetracycline resistance and porin osmoregulation, the transcriptional outputs in individual cells are graded functions of the applied stimuli. These systems are therefore examples of naturally occurring regulatory circuits that exhibit continuous control of transcription. Surprisingly, however, we find that porin osmoregulation is open loop; i.e., the porin expression level does not feed back into the regulatory circuit. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…To monitor transcription of the porin genes ompF and ompC, we used the two-color fluorescent reporter strain MDG147, which contains chromosomal operon fusions of yfp to ompF and cfp to ompC (5). We observed that colonies of MDG147 growing on medium A agar plates initially showed uniform CFP and YFP fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…To monitor transcription of the porin genes ompF and ompC, we used the two-color fluorescent reporter strain MDG147, which contains chromosomal operon fusions of yfp to ompF and cfp to ompC (5). We observed that colonies of MDG147 growing on medium A agar plates initially showed uniform CFP and YFP fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these findings, the effects of negative feedback (NF) on gene expression are not fully understood. For example, it was suggested that NF alters the shape of the dose-response curve in transcriptional cascades (22,25,26), but this effect has never been explored in detail. Such knowledge is vital for the rational design and characterization of increasingly complex transcriptional networks via bottom-up approaches in synthetic biology (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…New investigative approaches and mathematical analyses are revealing that regulatory complexity has important functional consequences, which include asymmetric kinetics (26), robust control (27), graded responses (28), and the generation of noise (29). As Emerson observed (30), ''The highest simplicity of structure is produced, not by few elements, but by the highest level of complexity.''…”
mentioning
confidence: 99%